Understanding Intercultural Communication Differences in the Workplace (Oratio Directa, 2020)
Different cultural backgrounds influence perception, message delivery, and interaction in the workplace. This article explains effective intercultural communication by examining low-context culture, high-context culture, and mindfulness. It uses a qualitative literature-review approach. The discussion indicates that intercultural communication requires respect for other people and cultures, recognition of their right to act differently, and a willingness to live together in diversity. Communication effectiveness also depends on the ability to understand explicit and implicit messages, reduce prejudice and ethnocentrism, and mindfully manage uncertainty and anxiety. Knowledge, cultural awareness, communication skills, and psychological adjustment help sustain harmonious intercultural interaction in the workplace.
Keywords: Intercultural communication; Mindfulness; Workplace; Cultural context; Communication competence